Hollywood As Historian : American Film in a Cultural Context - Browne, Ray B. (Ray Broadus), 1922-2009; Rollins, Peter C. (Book collections on Project MUSE., 1983)
Motion picture images have influenced the American mind since the earliest days of film, and many thoughtful people are becoming ever more concerned about that influence, as about the pervasive influence of television. In eras of economic instability and international conflict, the film industry has not hesitated to use motion pictures for definite propaganda purposes. During less troubled times, the American citizen's ability to deal with political and social issues has been enhanced or thwarted by images absorbed in the nation's theatres. Hollywood As Historian tracks the interaction of Ame.